Political Restructuring and Resource Control: Panaceas for Good Governance in Nigeria - Ghana, Arieja David; Akpomuvire, Mukoro; Princewill, Okereka Onofere (Master Program of Sociology, Universitas Malikussaleh, 2024)
Apart from the Boko Haram and Islamic State in West African Province (ISWAP) terrorism, banditry, kidnapping for ransoms, armed robbery, ritual killings, cybercrimes, attacks from unknown gunmen and Fulani herdsmen militancy, there is no issue in Nigeria in recent times that has attracted greater concern than the contestation for political restructuring and resource control conceived by many as panaceas for good governance. It is within this premise that study examined the fundamental causes of these contestations or agitations, and ascertained whether restructuring will serve the purpose for good governance in Nigeria. Descriptive analysis was adopted and qualitative method of data collection was utilised to gather materials for the study. This study finds it apposite to adopt Structural functionalism as its theoretical framework which its development is traced to Herbert Spencer, Emile Durkhein and Karl Marx, among others. The findings of this study revealed that the deepening contestations for political restructuring, resource control, constitutional amendment, and restoration of regional government by different groups, including professional bodies, trade unions, regional based groups and some section of the civil society is targeted at installation of true-federalism which is described by many as a panacea for good governance across the regions of the country, thus, this study finds it necessary to suggest that the government should overhaul the countrys political structure and provide constitutional backing for resource control to sub-national governments. There is also the need for decetralisation of the central which guarantees good governance at the grassroot levels.